Understanding Organizational Narrative-Counter-narratives Dynamics:: An overview of Communication Constitutes Organization (CCO) and Storytelling Organization Theory (SOT) approaches - Boje, David; Lundholt, Marianne Wolff (Communication & Language at Work, 2018)
There is a rich tradition of studying narratives in the fields of communication and language at work. Our purpose is to review two approaches to narrative-counter-narrative dynamics. The first is ‘storytelling organization theory’ (SOT), which interplays western retrospective-narrative ways of knowing with more indigenous ways of knowing called ‘living stories’, ‘pre-narrative’ and ‘pre-story’, and the prospective-‘antenarrative’ practices. The second is the communication as constitutive of organization (CCO) approach to narrative-counter-narrative. Both SOT and CCO deconstruct dominant narratives about communication and language at work. Both theories revisit, challenge, and to some extent cultivate counter-narratives. SOT seeks to go beyond and beneath the narrative-counter-narrative ‘dialectic’ in an antenarrative approach. CCO pursues counter-narratives as a useful tool to make tensions within and between organizations and society, salient as they may contest or negotiate dominant narratives, which hinder the organization from benefitting from less powerful counter-narratives.